PENGARUH SERVICE QUALITY, CUSTOMER SATISFACTION, DAN CUSTOMER VALUE TERHADAP CUSTOMER RELATIONSHIP MANAGEMENT QUALITY PADA CUSTOMER LOYALTY DEALER YAMAHA DENGAN BRAND IMAGE SEBAGAI VARIABEL MODERASI - Nico Adityo Utomo; Margaretha Pink Berlianto (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
The motorcycle automotive industry in Indonesia continues to grow and increase every year. Indonesia is a country with a rapidly growing motorcycle automotive industry in Southeast Asia. The development of this industry creates competition between motorcycle brands in Indonesia. The purpose of this study was to determine the effect of Service Quality, Customer Satisfaction, Customer Value on Customer Relationship Management Quality on Customer Loyalty from Yamaha dealers moderated by Brand Image. This study uses quantitative methods and data collection methods using Electronic & Online Questionnaires. The samples used were 272 samples using Convenience Sampling. The tool used to process data using PLS-SEM using SmartPLS software version 3.BAHASA INDONESIA ABSTRACTIndustri otomotif sepeda motor di Indonesia terus berkembang dan mengalami peningkatan setiap tahunnya. Indonesia merupakan negara dengan industri otomotif sepeda motor yang berkembang pesat di Asia Tenggara. Perkembangan industri ini menimbulkan persaingan antar brand sepeda motor di Indonesia. Tujuan dari penelitian ini untuk mengetahui pengaruh Service Quality, Customer Satisfaction, Customer Value terhadap Customer Relationship Management Quality pada Customer Loyalty dari dealer Yamaha dimoderasi oleh Brand Image. Penelitian ini menggunkaan metode Kuantitatif dan metode pengumpulan data menggunakan Electronic & Online Questionnaires memakai Google Form. Sampel yang digunakan sebanyak 272 sampel dengan menggunakan Convenience Sampling. Alat yang digunakan untuk mengolah data menggunakan PLS-SEM dengan memakai software SmartPLS versi 3.